If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (g + -7)(9g + -8) = 0 Reorder the terms: (-7 + g)(9g + -8) = 0 Reorder the terms: (-7 + g)(-8 + 9g) = 0 Multiply (-7 + g) * (-8 + 9g) (-7(-8 + 9g) + g(-8 + 9g)) = 0 ((-8 * -7 + 9g * -7) + g(-8 + 9g)) = 0 ((56 + -63g) + g(-8 + 9g)) = 0 (56 + -63g + (-8 * g + 9g * g)) = 0 (56 + -63g + (-8g + 9g2)) = 0 Combine like terms: -63g + -8g = -71g (56 + -71g + 9g2) = 0 Solving 56 + -71g + 9g2 = 0 Solving for variable 'g'. Factor a trinomial. (8 + -9g)(7 + -1g) = 0Subproblem 1
Set the factor '(8 + -9g)' equal to zero and attempt to solve: Simplifying 8 + -9g = 0 Solving 8 + -9g = 0 Move all terms containing g to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -9g = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -9g = 0 + -8 -9g = 0 + -8 Combine like terms: 0 + -8 = -8 -9g = -8 Divide each side by '-9'. g = 0.8888888889 Simplifying g = 0.8888888889Subproblem 2
Set the factor '(7 + -1g)' equal to zero and attempt to solve: Simplifying 7 + -1g = 0 Solving 7 + -1g = 0 Move all terms containing g to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -1g = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -1g = 0 + -7 -1g = 0 + -7 Combine like terms: 0 + -7 = -7 -1g = -7 Divide each side by '-1'. g = 7 Simplifying g = 7Solution
g = {0.8888888889, 7}
| d(2d-1)(3d+2)(8-d)=0 | | 4x+6+7x-7+20x-11=360 | | -4y+x=13 | | (d+9)(d+8)= | | =23+k | | (x-6)+5x=90 | | 217=7(1-5v) | | (5p-3)(4-p)(8p+1)=0 | | 7x+12+6x+13x-16=360 | | 5x^2-20=3x^2-60 | | a^2+4b^2= | | =-2(m+1) | | -12-15-b=1(b+48) | | y=2.5x+4.25 | | 3(x-4)=66*11 | | ?d=5 | | 5z-z+3= | | 4x+159=2x+153 | | 35-17=3x-6 | | -8-12=20 | | 18+3x-x^2=0 | | 33x-9=90 | | (-2w)(2w-3)(3w+10)=0 | | 4x^2-33x+48=-4x+3 | | 3(5c-3)-2=13c+1 | | 4x(2x+y)= | | 6x+21=90 | | 4x+17=-17 | | 8x^2+2n-15=0 | | m(4-m)(5+m)=0 | | y=12.8x+24 | | 11b+7=50 |